Methylation levels of the SCD1 gene promoter and LINE‐1 repeat region are associated with weight change: An intervention study. Issue 7 (15th May 2014) - Martín‐Núñez, Gracia María; Cabrera‐Mulero, Rebeca; Rubio‐Martín, Elehazara; Rojo‐Martínez, Gemma; Olveira, Gabriel; Valdés, Sergio; Soriguer, Federico; Castaño, Luis; Morcillo, Sonsoles
<x xml:space="preserve">Abstract</x> Scope Epigenetic processes may be affected by environmental factors. DNA methylation measured in LINE‐1 elements (LINE‐1, long interspersed nucleotide element‐1) correlates with LINE‐1 DNA methylation. Variations in stearoyl CoA desaturase (SCD) activity (a key enzyme in the fatty acid metabolism) may be involved in various processes that can lead to diseases such as obesity. We evaluated whether changes in diet after a nutritional intervention would be associated with changes in LINE‐1 DNA methylation and/or specific methylation of SCD1 gene promoter. Methods and results Design: Prospective cohort intervention study with a control group. We recorded phenotypic, anthropometric, biochemical, and nutritional information at baseline and 1 year later. DNA methylation was quantified by pyrosequencing. LINE‐1 DNA methylation and SCD1 gene promoter methylation levels were similar at the beginning of the study in both populations, whereas after a year these levels were higher in the control group (p < 0.001). In the intervention group, those subjects who lost weight showed higher levels of SCD1 gene promoter methylation after the intervention. Subjects with lower adherence to a Mediterranean diet experienced larger changes in LINE‐1 methylation. Conclusion DNA methylation levels were associated with weight change and with adherence to a Mediterranean diet.